Allgemeines deutsches Handelsgesetzbuch : Nebst Einf. - U. Erg. -Gesetzen unter Ausschluß D. Seerechts; Text-Ausg. mit Anm. ... U. Sachreg. - Litthauer, Felix (Walter De Gruyter Incorporated, 1894)
To celebrate the 270th anniversary of the De Gruyter publishing house, the company is providing permanent open access to 270 selected treasures from the De Gruyter Book Archive. Titles will be made available to anyone, anywhere at any time that might be interested. The DGBA project seeks to digitize the entire backlist of titles published since 1749 to ensure that future generations have digital access to the high-quality primary sources that De Gruyter has published over the centuries.
Keywords: Commercial law -- Germany.; LAW -- General.; Commercial law; Germany; Electronic books.